Распределение и численность большого баклана (Phalacrocorax carbo sinensis) на северо-западном побережье Азовского моря и Сиваше - Сиохин, В.Д. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Main colonial settlements of the Cormorant within the study area are situated in the wetlands of international importance "Bay of the Berda River, Berdyanskiy Bay and Berdyanskaya Spit", "Obitochnaya Spit and Obitochny Bay", "Molochnyi Liman", "The Central Sivash", "The Eastern Sivash" and also at the coastal areas of Arabatskaya Spit in the Sea of Azov (islands-ships and gas-derricks), in Aktashskoe Lake and in plantations of trees of the Mysovskoe forestry on Kerch Peninsula. Breeding settlements of the Cormorant on the north-western coast of the Sea of Asov and in the Sivash form a significant part of breeding population of this species and in the South Ukraine they are main areas by the number of breeding colonies and numbers of breeding birds.